Perkembangan Lembaga Pendidikan Islam: Tantangan dan Strategi Peningkatan Mutu - Vera Siti Magfiroh; Yurna Yurna; Ressy Resviati Putri; Ridwan Hermawan; Hendi Supandi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to examine the development of Islamic educational institutions in Indonesia from the classical to the modern era, as well as the factors influencing their transformation and strategies for strengthening them to remain relevant to contemporary needs without abandoning Islamic values. The research method used is a literature review (library research) by analyzing books, scientific journals, and official documents related to Islamic education, both nationally and internationally, published within the last five years. The findings indicate that Islamic education evolved from informal learning through majelis taklim, surau, and langgar, to the establishment of pesantren, madrasahs, and modern Islamic higher education institutions that integrate religious and general knowledge. The transformation of these institutions is influenced by local cultural factors, international scholarly networks, political pressures and colonialism, reformist figures, globalization, economic demands, social mobility, and national education policies. In the era of globalization and the Fourth Industrial Revolution, Islamic educational institutions face challenges such as technological access disparities, limited teacher competence in digital pedagogy, curriculum integration, and the risk of educational commodification. Strengthening strategies include developing integrative curricula, professionalizing teachers, utilizing digital technology, promoting media literacy based on Islamic values, developing entrepreneurship, revitalizing traditional knowledge, and enhancing alumni networks and visionary leadership. This study emphasizes that the synergy among pesantren, madrasahs, and Islamic higher education institutions forms a national Islamic education ecosystem that is adaptive, rooted in spiritual values, and capable of producing Muslim generations who are morally upright, knowledgeable, and globally competitive.